Health status of perimenopausal and postmenopausal women at Mangalore, Karnataka, India - C V Divya; Vasantkumar V Bhanushali; E Vinu; K S Premlal (Apollo Medicine)
Objectives: Women spend approximately one-third of their lives postmenopausal due to increased life expectancy. In this study, the daily activities of the study participants were associated with menopausal symptoms. Methodology: The women aged between 40 and 60 years residing in Mangalore town were selected as subjects for the current community-based cross-sectional study. The study participants were either going through natural menopause or had attained natural menopause. The data include sociodemographic profile, marital history, obstetric history, history of contraceptive use, history of chronic diseases, habits, physical activity, menstrual history, and menopausal symptoms. In addition, the individual effect of these variables on daily activities was noted among the participants. The investigator also examined the patients and measured the relevant anthropometric measurements along with the record. Results: The total number of study participants in the current research was 364. The most prevalent menopausal symptoms are night sweats (72.8%), irritability (94.2%), vaginal dryness (76.7%), decreased libido (94.8%), and fatigue (88.7%). The common comorbidities were anemia (49.5%), dental caries (23.4%), and hypertension (23.1%). There is a significant association between age at menopause (P < 0.05) and factors such as religion, socioeconomic status, age at menarche, length of menstrual cycles, number of bleeding days per cycle, history of oral contraceptive pill use, parity, age at first childbirth, and occupation (beedi workers). The women's daily activities (P < 0.05) in this age group were affected by the most familiar menopausal symptoms, including fatigue and irritability.